Implementasi Model Pembelajaran Small Group Discussion dengan Media Video Interaktif dalam Pembelajaran IPAS - Dewi Susilowati; Sukarno Sukarno; Karsono Karsono (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2025)
This study aims to evaluate the effectiveness of the small group discussion (SGD) learning metode based on interactive video media in improving the engagement and learning outcomes of elementary school students. The method used is descriptive qualitative research with a case study approach. Data were collected through observations, interviews, and thematically analyzed documentation. The results of the study show that the SGD learning metode allows students to be more active in discussing, exchanging opinions, and building understanding of concepts collaboratively. The use of interactive video media increases the appeal of learning, facilitates the understanding of concepts, and strengthens students' motivation to actively participate. Compared to the lecture method, the SGD metode showed increased student involvement, confidence, and better understanding of the material. However, there are challenges such as the variety of student participation, the limitations of technological facilities, and the need for teacher guidance in managing discussions. Therefore, this study recommends improving technology-based learning facilities, teacher training, and learning differentiation strategies. The implications of this study highlight that the interactive video-based SGD metode can be an innovative approach in improving the quality of learning in primary schools and is worthy of further study. Keywords: Small group discussion, interactive video, IPAS learning, Kurikulum Merdeka